Développement et palmier à huile : les enjeux de la gestion des territoires coutumiers ibans du Sarawak, Malaysia - Jean-François Bissonnette (VertigO)
The territory of Sarawak, state of East Malaysia, undergoes major environmental transformations. The fast social and economic reconfiguration of rural space is triggered by the rapid expansion of oil palm plantations, pursued officially for development purposes. In order to appraise this dynamic, the author focuses on a governmental project which aim is to convert most of customary native lands of Sarawak into oil palm plantations. The study allows comparing and confronting the semi-traditional iban organizational system of resource management to the modernist project put forward by the state. The observations realised allow addressing the notion of development from a critical perspective in the complex social and institutional context of Sarawak. Problems related to development schemes encountered locally and their causes are emphasised.